Implementation of the Culturally Responsive Teaching Approach to Improve Student Learning Outcomes in Pancasila Education in Grade IV at SDN 2 Tatura - Ni Made Riastini; Arif Firmansyah; Muchdar Muchdar; Herlina Herlina; Muslim Muslim (Journal of Educational Sciences, 2026)
This study aimed to improve the learning outcomes of fourth-grade students in Pancasila Education through the implementation of Culturally Responsive Teaching (CRT) at SDN 2 Tatura. The study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The study involved 35 fourth-grade students and was conducted in two cycles, with two meetings in each cycle. Data were collected through teacher and student activity observation sheets and learning outcome tests and were analyzed descriptively. The initial assessment showed that 11 students achieved the minimum mastery criterion, corresponding to a classical mastery level of 31.43%. In Cycle I, 23 students achieved mastery, resulting in a classical mastery level of 65.71%. In Cycle II, the number of students achieving mastery increased to 31, resulting in a classical mastery level of 88.57%, exceeding the predetermined success criterion of 80%. The improvement in learning outcomes was accompanied by increased teacher activity and student participation, particularly in contextual discussions, collaboration, expressing opinions, and presenting learning outcomes. These findings indicate that Culturally Responsive Teaching can support meaningful and participatory learning while improving learning outcomes in Pancasila Education.